Efficacy and Safety of Spesolimab in Patients with Generalized Pustular Psoriasis: A Subgroup Analysis of Chinese Patients in the Effisayil 1 Trial - Tsen-Fang Tsai; Min Zheng; Yangfeng Ding; Zhiqi Song; Quanzhong Liu; Ying Chen; Hanzhao Hu; Jinhua Xu (Adis, Springer Healthcare, 2023)
Abstract Introduction Generalized pustular psoriasis (GPP) is a rare and potentially life-threatening skin disease. The global Effisayil 1 study investigated the efficacy and safety of spesolimab, a humanized monoclonal antibody targeting the IL-36 receptor, in patients experiencing GPP flare. This analysis aimed to explore the efficacy and safety of spesolimab in the Chinese subgroup of Effisayil 1. Methods Effisayil 1 was a multicenter, randomized, double-blind, placebo-controlled phase II study. Eligible patients with a GPP flare were randomly assigned (2:1) to receive a single intravenous dose of spesolimab (900 mg) or placebo on day 1. On day 8, patients who had persistent symptoms that met a predefined criterion could receive open-label spesolimab. After day 8, patients with recurrent flares following clinical response could receive rescue treatment with open-label spesolimab. The primary end point was a Generalized Pustular Psoriasis Physician Global Assessment (GPPGA) pustulation sub-score of 0 at week 1. The key secondary end point was a GPPGA total score of 0 or 1 at week 1. Results Eleven Chinese patients were randomized, with five patients receiving spesolimab and six receiving placebo. At week 1, 60.0% (3/5) of patients in the spesolimab group and 16.7% (1/6) of patients in the placebo group achieved a GPPGA pustulation sub-score of 0 (risk difference 43.3%; 95% CI -22.6, 86.2); 60.0% and 16.7% of patients in the spesolimab and placebo group, respectively, achieved a GPPGA total score 0 or 1 (risk difference 43.3%; 95% CI -22.6, 86.2). Overall, four patients in each group of the spesolimab and the placebo groups reported at least one adverse event (AE) by week 1, with two and three reporting drug-related AEs, respectively. One patient reported a serious AE that was not considered to be drug related. No death occurred during the study period. Conclusion In the Chinese subgroup of the Effisayil 1 study, more patients receiving spesolimab experienced lesion clearance than those on placebo at week 1, with an acceptable safety profile that was consistent with the global study population. Trial Registration NCT03782792.